2014
DOI: 10.1155/2014/726190
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Alternative Methods for Toothbrush Disinfection: AnIn VitroStudy

Abstract: Objective. This study aimed to evaluate the effectiveness of alternative methods for toothbrush disinfection. Methods. Two-hundred eighty toothbrushes were included in the study. The toothbrushes were divided into 7 groups and were contaminated by standardized suspensions of Lactobacillus rhamnosus (L. rhamnosus), Streptococcus mutans (S. mutans), Staphylococcus aureus (S. aureus), and Escherichia coli (E. coli). The following disinfectants were tested: 1% sodium hypochlorite (NaOCl), 100% and 50% white vinega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 24 publications
2
19
0
8
Order By: Relevance
“…On the other hand, the toothbrushes sprayed with 1% sodium hypochlorite presented no S. mutans growth. This result is in agreement with the findings of previous studies 22,24 , in which there was absence or low percentage of S. mutans growth on toothbrushes after using this solution to disinfect the bristles. Sodium hypochlorite has bactericidal and fungicidal effect on the surface and depth of biofilm.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, the toothbrushes sprayed with 1% sodium hypochlorite presented no S. mutans growth. This result is in agreement with the findings of previous studies 22,24 , in which there was absence or low percentage of S. mutans growth on toothbrushes after using this solution to disinfect the bristles. Sodium hypochlorite has bactericidal and fungicidal effect on the surface and depth of biofilm.…”
Section: Discussionsupporting
confidence: 93%
“…Such results are compatible with a study showed that the concentration (60.5ml/100ml) vinegar was effective in when samples were immersed for one hour [31], while incompatible with study of Hayder et al [35] who reported that apple cider vinegar (5%) has significant antifungal effect against C.albicans and Non-C. albicans when compared with the negative control. White vinegar was found to be inefficient in reduction of the number of C. albicans colonies that adhered to specimens [29], however Peker et al [36] have reported that white vinegar was the most effective disinfecting agent for tested microorganisms and acrylic resins. C. albicans revealed full sensitivity of each of hydrogen peroxide, detol and lugol's iodine (Table 2) at all concentration 1%-5%.…”
Section: Activity Assay By Agar Diffusion Well Methodsmentioning
confidence: 96%
“…In view of low toxicity, low cost and a viable home-use application, apple vinegar and hydrogen peroxide showed the best antimicrobial activity against reference strains in screening tests (agar well diffusion and MIC/MMC evaluation). Vinegar and hydrogen peroxide have been suggested as interesting alternatives for the disinfection of other materials 19,20,[25][26][27][28][29] .…”
Section: Discussionmentioning
confidence: 99%